2020
DOI: 10.1371/journal.pone.0240934
|View full text |Cite
|
Sign up to set email alerts
|

Fulfillment, burnout and resilience in emergency medicine—Correlations and effects on patient and provider outcomes

Abstract: Background Healthcare provider wellness have been reported to correlate with patient care outcomes. It is not understood whether synergistic effects may exist between them. Objective We aim to investigate three provider wellness markers and determine their associations with provider self-reported medical errors and intent-to-leave outcomes among Emergency Department (ED) providers. Design This is a multi-center retrospective study. Method Three wellness domains include professional fulfillment (PF), burnout (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A study of EPs that was conducted before the COVID-19 pandemic showed that less burnout and high resilience could reduce intentions to leave their job. 30 There are no data on burnout or resilience among Korean EPs from before the COVID-19 pandemic; however, the burnout possibly worsened because of low resilience. Therefore, severe burnout can be prevented by enhancing and maintaining resilience of EPs.…”
Section: Discussionmentioning
confidence: 99%
“…A study of EPs that was conducted before the COVID-19 pandemic showed that less burnout and high resilience could reduce intentions to leave their job. 30 There are no data on burnout or resilience among Korean EPs from before the COVID-19 pandemic; however, the burnout possibly worsened because of low resilience. Therefore, severe burnout can be prevented by enhancing and maintaining resilience of EPs.…”
Section: Discussionmentioning
confidence: 99%
“…Greater rates of comfort with telephone visit quality for established vs. new patients, may be related to familiarity with established patients. Providers with high personal resilience, high professional fulfillment, and low burn-out, tended to be more stable in their jobs 12 . A recent study showed that the burnout in physicians could be reduced using a mobile application to increase physician resilience 13 .…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] In revealing this information, respondents also outlined critical manifestations of burnout as a potential threat to the integrity of the healthcare workforce. [4,7,9,13,14] Comments acknowledged the inherent risk to self and oth-…”
Section: Discussionmentioning
confidence: 99%
“…[7,13] For some HCWs, feelings of burnout may strengthen the urge to quit, both the job and the profession. [4,14] Other factors may contribute to HCWs' career choice doubts, such as the fear and anxiety associated with caring for persons with an easily transmissible disease. [6] Since the start of the pandemic, many HCWs have struggled with the fear of infecting and losing loved ones and coworkers to the coronavirus disease (COVID-19).…”
Section: Introductionmentioning
confidence: 99%